The genealogy of taubiy Islam (Dadash) Balkarukov - Muslim I., Barazbiev (Kavkazologiya, 2025)
The peoples of the North Caucasus have long prioritized the preservation of genealogical infor-mation. In recent decades, there has been an increased interest in such expertise. The purpose of this article is to look into the genealogy of Taubi Islam (Dadasha) Balkarukov, a well-known Ka-rachay-Balkarian aristocrat. The following is based on published materials by travelers and scientists prior to October, as well as the writings of current Russian historians and ethnographers. A large portion of the re-search is based on documentary sources discovered by the author in the archives of the Kabardino-Balkarian Republic (hereinafter KBR), Krasnodar Territory, and Republic of North Ossetia-Alania (hereinafter RSO-A). The article features a generational painting by Taubiy Balkarukov in a straight falling line. The picture offers information on specific individuals who are Islam’s direct ancestors (Dadasha), as well as himself and his children. Some emphasis is placed on the bond with individuals who played crucial roles in the fates of both Islam’s forebears (Dadash) and him-self. The study explores the Balarukovs’ marriage relations with the aristocratic families of Balka-ria and Karachay, as well as other peoples from the North Caucasus. Some information about the genealogy of the Taubi Balkarukovs is inconsistent, as evi-denced by multiple versions of the legends documented by researchers before to October. Finally, the paper concludes that Islam (Dadasha) Balkarukov’s genealogy gives a lot of data for both pro-fessional scientists and history and ethnology enthusiasts to explore. However, this issue requires additional investigation.